Application of modern educational technologies in the training for the management of accidents with chemical hazards - Rutić, Srđan Z. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The article presents the application of modern educational technology in the training for the management of accidents with chemical hazards. It describes the ,,HeSPRO" software package created to integrate the functions of evaluation and prediction of the effects of hazardous substances both in chemical accidents and during the use of highly toxic substances. The assessment of the software package application was carried out based on hypothetical models. The chemical hazard assessment was carried out through the analysis of the obtained results. It was concluded that the software package provides optimal conditions for effective evaluation and prediction of the situation in chemical accidents with hazardous materials. Introduction The baseline data for the assessment and prediction of chemical situations in accidents caused by hazardous substances are: - Information regarding the accident (place and time of the accident, the nature of the accident), - Type or types of dangerous goods - Meteorological conditions. Information about the nature of accidents can be obtained through the results of previous reviews of potentially dangerous objects and by summarizing data for all forms of surveillance, military reports and information from various ministries and civil structures. Types of hazardous materials are determined by the use of technical equipment for surveillance of chemical contamination. If such resources and data are not available, the assumption on the type of hazardous materials can be made by analyzing data about the facility and by recognizing the symptoms of poisoned (or contaminated) personnel. Meteorological conditions significantly determine the contamination potential of particular hazardous materials. For the prediction of consequences of accidents it is necessary to know the speed and the direction of air ground layer (inversion, isotherm, convection), air temperature and soil surface. For the assessment and the prediction of chemical situations in accidents involving hazardous substances and the primary or secondary formation of clouds, it is necessary to determine / calculate the following (Lukovic, et al., 2004): - propagation depth of the primary and secondary clouds, - propagation of the zones, - display data on the map, - arrival times of clouds to a given line, - duration of chemical contamination, - assessment of open sources of water contamination. Some hazardous materials may be formed along the primary and secondary clouds. This case corresponds to diffuse dangerous substances whose boiling point is lower than the ambient temperature (ammonia, chlorine, vinyl chloride, and the like.) (Lukovic, Jokic-Jankovic, 1994, Calvert, England, 1984). The primary cloud is formed based on high blood pressure in the tank and the interaction of spilled hazardous materials with the ground surface and the surrounding air. The secondary cloud is created due to the gradual evaporation of spilled hazardous materials.. A complex mathematical model that describes the changes in the concentration of hazardous substance vapor in space and time for such a case is based on a physical model of real events during accidents and dispersion of vapor of hazardous materials. The results of the assessment of the chemical situation caused by accidents involving dangerous goods on the basis of complex models include a number of real phenomena accompanying the complex process of the formation and dynamics of accidents; for simpler reliefs, they are in good agreement with the experimental data, but require specially trained users and high-resource computing techniques. However, the nature of chemical accidents is such that they appear suddenly and often at unpredictable places (when transporting hazardous materials), so that the speed of action and a method of team engagement are the most important factors in the rehabilitation of accident consequences (Bursać, et al., 1990 Franke, 1977). Therefore, simple mathematical models are particularly suitable in such situations, because in the short term they provide an approximate assessment of emergency and serve as a basis for undertaking appropriate measures to protect the population, material resources and the environment (Marshall, 1987). Application of the "HeSPRO" software package for management in accidents involving dangerous goods A software package, ’’HeSPRO’’, was created with the intention to combine the functions of assessment and forecast of the effects of hazardous substances both in peacetime chemical accidents and during the use of highly toxic substances (Lukovic, et al., 2004). The purpose of the software package can be multiple, and the software may be used: - in military and civilian units and institutions whose business is tracking and elimination of the consequences, for rapid assessment of the vulnerability of zones where the accident occurred, or objects (units, population) in the zone of the accident; - for the elaboration of possible sources of danger (warehouses, storage tanks, transportation, industrial facilities, etc.); - for educational purposes (in NBC units, as well as in similar civilian institutions) to facilitate simulation in order to gain insight into how the parameters affect the development of the situation after the accident, as well as to learn the specifics of particular hazardous substances. The software for the applications mentioned can be used in peacetime and in wartime. Conclusion Regarding all the specifics of accidents during the production and transportation of highly toxic substances, it can be concluded that the organization of the response to this kind of accidents, as one of the priority tasks, is an extremely complex activity that requires full professional qualifications of all subjects and adequate training of staff who will be able to respond effectively to accidents involving hazardous substances. As for teaching, it can be concluded that the most appropriate form of teaching is the demonstration method, because it is closely associated with the technical side of teaching material which is very important in this case. One way of training the Army to respond to incidents involving hazardous materials is training officers to perform fast estimation and prediction of the situation with chemical accidents involving hazardous substances using the "HeSPRO" software package. For example, using a hypothetical model of the software package mentioned in this accident with hazardous materials shows that the application of modern educational technology in teaching and training is very important. The "HeSPRO" software package provides optimal conditions for effective assessment and prediction of chemical accidents involving hazardous substances, with the the purpose of monitoring and removing their consequences. Using this software package to reduce risk is very effective because it enables quick access to information on hazardous substances, the use of data for the evaluation of a particular situation and data transfer to competent authorities in order for them to respond adequately.The speed of response is thus enhanced and the operational management of accidents for the whole process increased  to a new level.
Keywords: assessment of the situation; software package; "HeSPRO"; hazardous materials; chemical accidents